Al-D?arûrat dalam Pandangan Yûsûf Qard?âwî - Syaiful Hidayat (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2014)
The priest Shâfi’î firmly reject istih?sân method as a basis in determining Islamic law. This rejection can be seen from the statement imam Shâfi’î istih?sân related practices undertaken by the sect H?anafî. Priest Shâfi’î said man istah?sana faqad shara’a. Priest Shâfi’î found istih?sân is legal determination with reasonable effort and passion alone. This is tantamount to allowing people who can not understand the nas?s? and qiyâs set with istih?sân law. As a result, will emerge fatwas based on the legal opinion of the intellect alone, as well as an effort to ignore the nas?s?. In the context of the rules by relying on logic alone, then this short article will outline some of the statements Yûsûf Qard?âwî in deciding the legal practice of abortion by using the concept of emergency approach.